Preparation of a Poly(ethylene glycol)-Based Cross-Linked Network from a Click Reaction for Enzyme Immobilization - OKTAY, BURCU; KAYAMAN APOHAN, NİLHAN; DEMİR, SERAP (WILEY-V C H VERLAG GMBH, 2019)
In this study, a polyethylene glycol (PEG)-maleimide film was prepared by a thiol-ene click reaction. The covalent immobilization of amylase was carried out onto the PEG-maleimide based photo-curable network via epoxy and C=O groups without any linker. The epoxy and carbonyl groups on the PEG backbone improved the affinity of the enzyme. The immobilization yield of amylase onto the film was 72.46%. The immobilization capacity was also determined as 313 mg/g. The thermal stability of amylase improved via covalent attachment. Immobilized amylase showed maximum activity at 40 degrees C and pH 6.5. The immobilized amylase continued to retain 66% of its initial activity after 30 days.
Keywords: amylase; click chemistry; enzyme immobilization; thiol-ene; ALPHA-AMYLASE; SUPPORTS; GLYCOL; PEG; FUNCTIONALIZATION; OPTIMIZATION; CONJUGATION; MALEIMIDES; STABILITY; KINETICS